Identifying augmented renal clearance in trauma patients: Validation of the Augmented Renal Clearance in Trauma Intensive Care scoring system. Issue 4 (April 2017) - Barletta, Jeffrey F.; Mangram, Alicia J.; Byrne, Marilyn; Sucher, Joseph F.; Hollingworth, Alexzandra K.; Ali-Osman, Francis R.; Shirah, Gina R.; Haley, Michael; Dzandu, James K.
Abstract : BACKGROUND: Augmented renal clearance (ARC) is common in trauma patients and associated with subtherapeutic antimicrobial concentrations. This study reported the incidence of ARC, identified ARC risk factors, and described a model to predict ARC (i.e., ARCTIC) that is specific to trauma patients. METHODS: Consecutive trauma patients who were admitted to the intensive care unit between March 2015 and January 2016 and had a measured creatinine clearance (CrCl) were considered for inclusion. Patients were excluded if their serum creatinine (SCr) was greater than 1.3 mg/dL. ARC was defined as a measured CrCl of 130 mL/min or greater. Demographic and trauma-specific variables were then compared, and multivariate analysis was performed. Using these results, a weighted scoring system was constructed and evaluated using receiver operating characteristic curve analysis. ARCTIC score cutoffs were chosen based on sensitivity, specificity, positive predictive value, and negative predictive value. The derived scoring system was then compared to a previously published scoring system for accuracy. RESULTS: There were 133 patients with a mean age of 48 ± 19 years and SCr of 0.8 ± 0.2 mg/dL. The mean measured CrCl was 168 ± 65 mL/min, and the incidence of ARC was 67%. Multivariate analysis revealed the following risk factors for ARC (age, <56: odds ratios [OR], 58.3; 95% confidence interval [CI], 5.2–658.9; age, 56 to 75: OR, 13.5; 95% CI, 1.2–151.7), SCr less than 0.7 mg/dL (OR, 12.5; 95% CI, 3–52.6), and male sex (OR, 6.9; 95% CI, 1.9–24.9). Using these results, the ARCTIC scoring system was: 4 points if younger than 56 years, 3 points if aged 56 years to 75 years, 3 points if SCr less than 0.7 mg/dL, and 2 points if male sex. Receiver operating characteristic curve analysis revealed an area (95% CI) of 0.813 (0.735–0.892) ( p < 0.001). An ARCTIC score of 6 or higher had a sensitivity, specificity, positive predictive value, and negative predictive value of 0.843, 0.682, 0.843, and 0.682, respectively. CONCLUSION: The incidence of ARC in trauma patients is high. The ARCTIC score represents a practical, pragmatic system that can be easily applied at the bedside. An ARCTIC score of 6 or higher represents an appropriate cutoff to screen for ARC where antimicrobial adjustments should be considered. LEVEL OF EVIDENCE: Prognostic/epidemiologic study, level III.